The role of business advisers in supporting social entrepreneurship. Issue 2 (24th September 2020) - Dalborg, Cecilia; von Friedrichs, Yvonne
Abstract : Purpose: In many regions, the potential of social entrepreneurship and social innovation are not fully used. The purpose of this study is to explore issues and challenges in the business advisory support offered to social entrepreneurs and, from this background, give suggestions on how the advisory process to social entrepreneurs could be modified to better gain society. Design/methodology/approach: Representatives from 15 business advisory organisations in Sweden were interviewed to examine how their support to social enterprises meets the needs of the companies, and to discover possible problems encountered regarding the business advice available to social enterprises. Using thematic analysis, six different overarching themes were identified that characterise issues and challenges in the business advisory support offered to social enterprises. Findings: The results show that many advisers lack experience in social entrepreneurship, yet they consider that social enterprises are not "genuine" entrepreneurs, and that they, therefore, refer them to advisers focussing on co-operative enterprises. Furthermore, the absence of sustainable business models, the lack of financial resources and the existence of municipal monopoly are identified by the advisers as challenges. Practical implications: This paper reveals an Achilles' heel in the business advisory support offered to social enterprises, namely, the lack of experience and knowledge of social entrepreneurship amongst current business advisers, as well as a prioritisation of advice to more "commercial" entrepreneurs because of policy instruments and the expectations from the public funders of increased profitability and growth in the companies that receive advice. The mainstream business advisory service could play a key role by bringing together the various stakeholders in this shared value process. This would, however, require increased knowledge and new government policies and directives that ensure that social entrepreneurs are prioritised in the business advisory situation. Originality/value: This paper demonstrates that the current advisory system is not adapted to fit the needs of social enterprises. It also proposes the need to include participation and proximity in the business model design.